Children & libraries : - Walter, Virginia A (American Library Association, 2001)
This book is for people who work with/for children in public libraries. The book provide a comprehensive overview of the history of library services to children, assesses the current state of the profession, and proceeds to lay out a far-reaching vision for the future. The author examines changing routines, educational practices, and social patterns that have had a profound effect on our communities and from these trends drafts a slate of suggested goals for those of us who strive to serve children. She also examines the impact of digital technology and looks at the future of the book.